Analysis Of Seed and Fertilizer Assistance Programs On Improving Corn Farmers - Abdul Latif; Mustani Mustani (Universitas Gorontalo, 2020)
The objectives of this study are: 1) Analyzing the income of corn farmers in Tabongo District. 2) Analyzing seed and corn assistance programs to increase farmers' income in Tabongo sub-district, Gorontalo district. This research will be carried out in Tabongo sub-district in Gorontalo regency with the time the research will begin in December 2018 until February 2019 with a sample of 31 farmers. The results showed that farmers' income on hybrid corn farming in Tabongo District was based on an average of Rp. 7,979,282 while based on the average/Ha of 5,496,839. With the seed and fertilizer assistance program in Tabongo District, it can increase the amount of income generated by farmers and can reduce the amount of costs incurred to buy seeds and fertilizer. Based on the results of calculations that have been done using multiple linear regression analysis obtained that the seed and fertilizer assistance programs simultaneously have a significant effect on increasing the income of corn farmers in Tabongo sub-district. Whereas the farmer assistance program to partially increase the income of corn farmers in Tabongo District, namely the seed and fertilizer variables, has a positive and significant effect on the increase in income of corn farmers in the Tabongo sub-district